2019
DOI: 10.1007/s40825-019-00127-0
|View full text |Cite
|
Sign up to set email alerts
|

Selective Catalytic Reduction of NOx over V2O5-WO3-TiO2 SCR Catalysts—A Study at Elevated Pressure for Maritime Pre-turbine SCR Configuration

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…This behavior is in line with literature [7,8] and emphasizes the positive effect of elevated pressure on the performance of a V-based SCR catalyst. Several studies [8,9] have shown that the pressure does not change the reaction kinetics and that the increased conversion with elevated pressure is affected by the negative impact of decreased diffusivity. For the small hydraulic diameter (1,27 mm) of the monolithic channels used in the present study, the higher residence time was the dominant factor leading to significantly improved NOx conversion.…”
Section: Influence Of Hydrocarbons On Catalytic Nh3-scr At Elevated P...mentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior is in line with literature [7,8] and emphasizes the positive effect of elevated pressure on the performance of a V-based SCR catalyst. Several studies [8,9] have shown that the pressure does not change the reaction kinetics and that the increased conversion with elevated pressure is affected by the negative impact of decreased diffusivity. For the small hydraulic diameter (1,27 mm) of the monolithic channels used in the present study, the higher residence time was the dominant factor leading to significantly improved NOx conversion.…”
Section: Influence Of Hydrocarbons On Catalytic Nh3-scr At Elevated P...mentioning
confidence: 99%
“…Kröcher et al [7] showed for a V-based catalyst that an increased pressure grants a significantly smaller catalyst volume but also that the decreased diffusion and increased partial pressures can hinder the standard SCR reaction. Experimental and modeling studies of Rammelt et al [8] and Christensen et al [9] indicated no change in catalytic activity and kinetics at elevated pressures, and only an increased adsorption of NH3 for V-based catalysts. In one of our earlier studies we reported the positive influence of pressure as well as the negative impact of propylene and SO2 for a Cu-SSZ-13 SCR catalyst.…”
Section: Introductionmentioning
confidence: 96%
“…The volumetric flow rate of the exhaust gas also suffers a direct variation and, consequently, the flow dwell time [27]. The dwell time increase improves the mass transfer of the pollutants toward the catalyst active sites, which implies higher conversion efficiency [28] and a reduction of the light-off temperature [29]. On the contrary, an increase in the volumetric flow rate reduces the dwell time, which decreases the conversion efficiency of the catalysts [30].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, one of the most important parameters promoting the catalytic reaction is temperature and numerous solutions proposed over the years include a closer location of the catalytic system towards the engine [13]. For instance, a very promising increase in activity 2 of 17 was obtained by positioning the NH 3 -SCR catalyst in front of the turbocharger [14][15][16][17]. In addition to temperatures of up to 180 • C higher at this location [18], the residence time is enhanced due to the higher pressure.…”
Section: Introductionmentioning
confidence: 99%